An association between autumn birth and clozapine treatment in patients with schizophrenia: A population-based analysis. (August 2014) - Sørensen, Holger J.; Foldager, Leslie; Røge, Rasmus; Pristed, Sofie Gry; Andreasen, Jesper T.; Nielsen, Jimmi
Abstract Background: Numerous studies on seasonality of birth and schizophrenia risk have been published but it is uncertain whether, among those with schizophrenia, refractory illness exhibits any predilection for birth month. We hypothesized and examined whether a season of birth effect was present in patients with schizophrenia with a history of clozapine treatment. Method: Using record linkage with Danish registers, we examined patients with schizophrenia born between 1950 and 1970, and between 1995 and 2009 and Cox regression analysis was used to examine season of birth in relation to history of clozapine treatment. Results: In a study population corresponding to 60, 062 person-years from 5328 individuals with schizophrenia of which 1223 (23%) received at least one clozapine prescription, birth in the autumn (September–November) was associated with clozapine treatment (HR = 1.24; 95% CI 1.07–1.46) when compared with birth in the spring (March–May). Conclusion: Although replication studies are needed, this is the first evidence from a nationwide study suggesting a possible season-associated risk of clozapine treatment in schizophrenia. The reasons for this relationship remain to be further investigated but might be partially explained by early exposures such as winter flu season and low vitamin D levels.